Bio-Based Composite Footbridge: Design, Production and In Situ Monitoring. Issue 3 (3rd July 2019) - Blok, Rijk; Smits, Joris; Gkaidatzis, Rafail; Teuffel, Patrick
Abstract: This paper deals with the design, production and monitoring of a bio-composite footbridge with a span of 14 m across the river Dommel in the city of Eindhoven, the Netherlands. The specific bio-composite material that was used for this research is a Natural Fibre Reinforced Bio-Polymer (NFRBP). The goal of the research is to prove that NFRBP can be applied as a load-bearing structure in an outdoor environment. For this purpose, a multidisciplinary team of academic researchers from two universities and from the Centre of Expertise Biobased Economy, together with a manufacturer from the NFRBP industry, have developed a feasible design that could be produced in a short period of time and within a limited budget. The footbridge was designed, built and installed within less than one year. In the two years after the installation of the footbridge, the structural behaviour of the bridge was monitored by means of optical fibre glass strands, integrated within the structure, with the purpose of measuring deformations and change in elasticity that occur over time.